Maciez da carne bovina e sua relação com o crescimento e os tipos de fibra musculares - Hadlich, Janaina Conte [UNESP]; Curi, Rogério Abdalah [UNESP]; Silva, Maria Gabriela Berchiol da [UNESP]; Factori, Marco Aurélio [UNESP]; Silveira, Antônio Carlos [UNESP]; Chardulo, Luis Artur Loyola [UNESP] (Pontificia Universidade Catolica do Parana - PUCPR, 2013)
The Brazilian livestock industry is passing through an important moment in history, over passing the barrier of a commodity-based industry to a livestock market that produces differentiated and standardized quality products. Thus, the livestock industry needs to show efficiency from the farm all the way through the consumer, who could be Brazilian or a foreigner of a country that imports Brazilian beef. Despite this notable position in the global economic scenario, the national livestock, which is compose mainly by Bos indicus cattle, is characterized by having a production yield that falls short to the full potential of the country’s production system. In addition, there is great variation in the meat quality, which may undermine the competitiveness of Brazilian products in the global market. Countless factors can influence the final quality of beef products, especially tenderness, which is one of the most desired characteristics from the consumers’ perspective. Animal growth, which is represent by the expansion in body size and the composition of the fibers from the skeletal muscle, is one of the key features that can be used to forecast and justify the quality of beef. Therefore, the objective of this review was to evaluate the influence of muscle fiber characteristics and animal growth in beef tenderness.

A pecuária brasileira passa por um momento de grande importância, atravessando a barreira de uma pecuá- ria produtora de commodities para uma pecuária que elabora produtos diferenciados, padronizados e com qualidade. E, para isso, a pecuária precisa mostrar-se eficiente desde a produção dos animais até o produto que chegará à mesa do consumidor, seja ele brasileiro ou consumidor dos países importadores da carne brasileira. Apesar dessa posição de destaque no cenário econômico, a pecuária de corte nacional, composta, principalmente, por bovinos Bos indicus, se caracteriza por apresentar uma produtividade aquém de todo o potencial que pode expressar, além de apresentar grande variação na qualidade da carne, fatos que podem comprometer a competitividade do produto brasileiro no mercado mundial. São inúmeros os fatores que podem influenciar na qualidade final da carne bovina, em especial a maciez, que é uma das características mais desejadas pelos consumidores. Dentre os fatores que influenciam nas características da carne bovina, o crescimento do animal, ou seja, a ampliação da dimensão e a composição das fibras do tecido muscular esquelético dos bovinos é um dos fatores que pode ser utilizado no entendimento e justificativa quanto à qualidade da carne bovina. Neste sentido, o objetivo desta revisão foi avaliar a influência dos tipos de fibras musculares e do crescimento na maciez da carne bovina.
Relationship of meat tenderness with muscle fibers and cattle growth
Keywords: Beef cattle; Bos indicus; Meat quality; Superprecoce bullocks; Bos indicus; Bovinos de corte; Novilho superprecoce; Qualidade de carne